(untitled) (Innovative professional education, 2024)
The subsection describes the approaches to defining the essence and structure of monitoring the quality of education, provides a list of regulatory documents on the mechanisms for preparing and conducting monitoring of the quality of education and educational activities in educational institutions, and provides a justification for the principles of organising monitoring of the quality of education in the context of vocational education in a blended learning environment.